2017
DOI: 10.1016/j.jbiomech.2017.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to buffer solution alters tendon hydration and mechanics

Abstract: A buffer solution is often used to maintain tissue hydration during mechanical testing. The most commonly used buffer solution is a physiological concentration of phosphate buffered saline (PBS); however, PBS increases the tissue’s water content and decreases its tensile stiffness. In addition, solutes from the buffer can diffuse into the tissue and interact with its structure and mechanics. These bathing solution effects can confound the outcome and interpretation of mechanical tests. Potential bathing soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…The biphasic nature of connective tissues provides a demonstrated mechanism in which fluid content and fluid flow relative to the solid tissue structure can both influence quasistatic tissue mechanics and impart rate-dependent behavior ( 19 , 20 ). To investigate whether a fluid flow–based mechanism could explain the observed rate-dependent fatigue resistance, we performed finite-element simulations using an anisotropic, high Poisson’s ratio permeable elastic solid with a mobile fluid phase ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The biphasic nature of connective tissues provides a demonstrated mechanism in which fluid content and fluid flow relative to the solid tissue structure can both influence quasistatic tissue mechanics and impart rate-dependent behavior ( 19 , 20 ). To investigate whether a fluid flow–based mechanism could explain the observed rate-dependent fatigue resistance, we performed finite-element simulations using an anisotropic, high Poisson’s ratio permeable elastic solid with a mobile fluid phase ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings have been reported by Safa, et al . 35 , who found significant alterations in modulus and equilibrium stress of rat tail tendon fascicles following an 8-hour submersion in 0.9% saline solution. Their study consequently recommended against using saline buffer solutions in favor of PEG-based solutions 35 .…”
Section: Discussionmentioning
confidence: 99%
“…36 and Safa, et al . 35 . Nevertheless, there was no significant change in strain at maximum force at the various water contents investigated in the macro mechanical tests carried out here.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, collagen fibrils in tendons and ligaments are more aligned and stiffer than fibrils from the AF (Cassidy et al, 1989;Lynch et al, 2003). These differences in tissue composition are related to a limited overall swelling capacity (~10% increase in tendon volume in saline verses~40% increase in AF volume) (Adams, 2004;Amiel et al, 1983;Henninger et al, 2010;Iatridis et al, 2007;Riley et al, 1994;Safa et al, 2017). Our findings showed that tissues with fibers aligned in a single direction (i.e., no cross-ply pattern) have less ability to resist matrix swelling.…”
Section: Discussionmentioning
confidence: 76%